Chronic oral administration of ibrutinib prevents long-term memory deficits and reduces AD pathology and neuroinflammatory responses in a mouse model of AD - Hyun-ju Lee; Sora Kang; Yoo Joo Jeong; Jin-Hee Park; Jeong-Woo Hwang; Chan-Hu Gu; Tae-Mi Jung; Seokjun Oh; Ji-Yeong Jang; Hyang-Sook Hoe (Molecular Brain)
Abstract We previously demonstrated that ibrutinib has therapeutic efficacy against AD pathologies when injected intraperitoneally at a lower dosage (10 mg/kg, daily for 2 weeks) or orally at a higher dosage (30 mg/kg, daily for 1 month) in AD mice models. However, the effect of chronic lower dose of ibrutinib by oral administration on AD pathologies has not been investigated yet. Therefore, we investigated whether long-term oral administration of ibrutinib at a lower dose (1 or 10 mg/kg, daily for 5 months) on AD pathology and in vivo toxicity in 5xFAD mice. We found ibrutinib enhanced cognitive function and alleviated Aβ pathology in 5xFAD mice without hepatotoxicity. Furthermore, ibrutinib-treated 5xFAD mice decrease tau hyperphosphorylation, p-GSK3α/β levels, and markers of neuroinflammation such as Iba-1, GFAP, and NLRP3. Collectively, these translational studies indicate chronic oral administration of ibrutinib at low doses improves cognitive function and suppresses AD pathology/neuroinflammation in an AD mice model thereby having potential as an effective multitarget AD therapeutic in clinical application.